(untitled) (American Journal of Islam and Society, 1989)
The volume under review is essentially a collection of papers presented at a two-day workshop on the changing division of labor in South Asia held at the University of Wisconsin in 1984 at which the two major themes were the emerging role of women; and the “increasingly violent role of religion.”I The latter theme became the subject of this book. Concerning this subject, the editor, Dr. Bjorkman, writes: “If, then, you have been perplexed about the chronic religious violence in contemporary South Asian states, you need search no further for relief. The following chapters examine, explore, and explain aspects of religious fundamentalism, self-righteous revivalists, and murderous mayhem among the four major faiths of South Asia." Then, evincing his concern for the human situation in the area, and his own obviously painful experiences there, Dr. Bjorkman continues: “. . . one may justifiably conclude that a no-win situation characterizes the South Asian mosaic. Contemporary reality is depressing, if not gruesome; the daily documentation of death and destruction, cruelty and carnage, is sufficient evidence thereof? Candidly assessing the objective of his work, Dr. Bjorkman states: “The aim of this book is to uncover some of the socio-political truths disguised by the frequent invocation of “fundamentalist” and “revivalist” claims in contemporary South Asian religions.” And in order to prepare the reader for what lies ahead, the learned editor adds: “One can come away from this volume wringing one’s hands in despair at the utter hopelessness of human foibles. Or one can catch glimpses of truth and possible points of leverage by which the certain slide into anarchy might be arrested and even reversed. Sigmund Freud once wrote: ‘The truths contained in religious doctrines are after all so distorted and systematically disguised that the mass of mankind cannot recognize them as truth (Freud 1928 :78) .“ Thus, before moving on to even the editor’s introductory chapter, the interested reader, in the sense of his or her faith or allegiance to one or the other of the four major religions of South Asia, will begin to feel queasy at the prospect of what lies ahead. Many such, I suspect, will put the volume down and start wringing their own hands at the utter hopelessness of human foibles in the guise of Western academic treatments of Eastern affairs of the spirit. But no, gentle reader, dismay not; the volume is not your average witch hunt. On the contrary, as food for thought it is immediately engaging, and as an opportunity for self-exam ...